PERAN PENTING MASYARAKAT DALAM PARTISIPASI PENINGKATAN MUTU PENDIDIKAN AGAMA ISLAM DI MADRASAH - Hartono Hartono (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
The role of the community to madrasah is important to create an qualified Islamic education that is participation in participating to develop the quality of education, participation among communities can do are (1) Community participation in management; include public participation in drafting the madrasah and public participation in appointment of school principals, school committees and others. (2) Public participation in the curriculum; include public participation, in implementing local curriculum, and community participation in the determination of the holiday. (3) Public participation in student recruitment; done by some community leaders to work together with teachers, before the New Year or before the lesson. (4) Public participation in the provision of funds, facilities and infrastructure; includes funding for the implementation costs for the provision of education facilities and infrastructure. (5) Public participation in the course of religious life in the madrasah. This participation of community leaders’ participation in religious activities in Madrasah. (6) Public participation in employment.